2020
DOI: 10.1262/jrd.2019-147
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hyperstimulation affects the ultrastructure of mouse fallopian tube epithelium

Abstract: Controlled ovarian hyperstimulation (COH) is routinary used in assisted reproductive technologies (ARTs) to increase the yields of mature oocytes. The possibility that patients with a history of failures or poor-responders may develop side-effects following these treatments is still debated. Epidemiological studies reported controversial results about pregnancy outcome and the risk of developing gynecological cancers. By using a mouse model, here we compared the ultrastructural features of fallopian tubes (FTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…These results showed that repeated ovarian stimulation prolongs the luteal phage in which the CL develops. A recent report showed that repeated ovarian stimulation at 16-day intervals alters the estrus cycle, inducing uterine cell proliferation in mice (Antonouli et al, 2020). In monkeys, however, observations of the uterus after 5 years of repeated ovarian stimulation did not result in significant changes in the endometrium (Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…These results showed that repeated ovarian stimulation prolongs the luteal phage in which the CL develops. A recent report showed that repeated ovarian stimulation at 16-day intervals alters the estrus cycle, inducing uterine cell proliferation in mice (Antonouli et al, 2020). In monkeys, however, observations of the uterus after 5 years of repeated ovarian stimulation did not result in significant changes in the endometrium (Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The small number of patients undergoing COS > 5 times in the clinic makes statistical analysis di cult, whereas a distinctive study can be designed to analyze them in an animal model. Antonouli et al [20] reported that the oviducts of mice receiving 4 and 8 gonadotropin stimulation did not perceive signi cant morphological changes but underwent signi cant ultrastructural alterations, including a dramatic decrease in ciliated cells and massive mitochondrial degeneration compared to controls (who did not receive stimulation). These alterations were more pronounced at 8 than 4 times, which may negatively affect the fertilization process and embryo transport to the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…For light microscopy (Zeiss Axioscope, Gottingen, Germany) observation, methylene blue staining (Sigma-Aldrich) was used for coloration of semithin sections (1 μm); for TEM (Zeiss EM10, Oberkochen, Germany), operating at 60 kV, ultrathin sections (90–100 nm) were cut with a diamond knife, mounted on copper grids, contrasted with Uranyless (Uranyl acetate alternative) (TAAB Laboratories Equipment Ltd., Aldermaston, UK) and lead citrate (Electron Microscopy Sciences), and photographed. Further details of sample preparation for TEM observations have been reported elsewhere, in our previous studies [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%